Origin, Development and Decline of Monolithic Pillars and the Continuity of the Tradition in Polylithic, Non-Lithic and Structural Forms. (18th February 2016) - Krishnamurthy, S.; Tiwary, Sachin Kr.
The present paper deals with one such creations of Man, i.e. the tradition of erecting free standing monolithic pillars - its origin, growth and decline and the continuity of the tradition of erecting such pillars in its changed polylithic (from Greek word polloi = many + lithic = stone), non-lithic and structural forms. No exact reason can be found, pointing it to be the exact cause for the decline in the tradition of erecting monolithic pillar and its transformation. In this paper the authors try to analyse various phenomenon likesocio-political, economic and technical aspects which may have lead to their decline and subsequently their continuity in a changed form in Indian context.